RUANG BERUBAH BERSAMA-SAMA: ANTROPOLOGI DALAM TRANSFORMASI SOSIAL BUDAYA PAPUA - I Ngurah Suryawan (Studi Budaya Nusantara, 2018)
AbstrakThe biggest challenge of anthropology, especially in frontier areas (front lines) like in Papua, is to place it in the context of the vortex of the meaning of socio-cultural transformation experienced by humans themselves. Anthropology, thus becoming a "weapon" in the face of the inevitable social and cultural changes. This article reflects the power of ethnography in the long span of the journey of reproducing Papuan cultural knowledge. This study argues that ethnographic reproduction produced with a colonialistic perspective will lack power and language in describing the complexity and transformation of culture in the Land of Papua. The reality of the Papuan people is high mobility, interconnected with other cultural ethnicities with cultural diversity, and their relationship with the power of global investment. It was during these meeting moments that the Papuan people had the opportunity to think about their renewal of identity and culture.AbstractThe biggest challenge of anthropology, especially in frontier areas (front lines) like in Papua, is to place it in the context of the vortex of the meaning of socio-cultural transformation experienced by humans themselves. Anthropology, thus becoming a "weapon" in the face of the inevitable social and cultural changes. This article reflects the power of ethnography in the long span of the journey of reproducing Papuan cultural knowledge. This study argues that ethnographic reproduction produced with a colonialistic perspective will lack power and language in describing the complexity and transformation of culture in the Land of Papua. The reality of the Papuan people is high mobility, interconnected with other cultural ethnicities with cultural diversity, and their relationship with the power of global investment. It was during these meeting moments that the Papuan people had the opportunity to think about their renewal of identity and culture.